1981
DOI: 10.1021/jo00328a020
|View full text |Cite
|
Sign up to set email alerts
|

Catechol and substituted catechol-derived ortho esters, models for protected active esters in peptide synthesis

Abstract: was washed three times with 25-mL portions of water, twice with 25-mL portions of 5% aqueous K2C03, and finally with saturated salt solution. The organic layer was dried over MgS04 and concentrated.l-Acetoxy-2-nitro-3,3,5,5-tetramethylcyclohexene was isolated by fractional crystallization from ether at low temperatures, and after recrystallization from ether 0.75 g of white crystals was obtained: mp 84-85 °C;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The orthoester is an extremely versatile structural feature, used as a protective group for esters in peptide synthesis and for alcohols in nucleoside synthesis . This functional group is vital for transformations such as the Claisen‐Johnson rearrangement, the synthesis of a variety of nitrogen‐based heterocycles and various condensation reactions .…”
Section: Methodsmentioning
confidence: 99%
“…The orthoester is an extremely versatile structural feature, used as a protective group for esters in peptide synthesis and for alcohols in nucleoside synthesis . This functional group is vital for transformations such as the Claisen‐Johnson rearrangement, the synthesis of a variety of nitrogen‐based heterocycles and various condensation reactions .…”
Section: Methodsmentioning
confidence: 99%
“…This mechanism is well-accepted by many researchers including computational chemists . However, in 1981, Vellaccio and Kemp, based on their experiment results, showed some skepticism toward this mechanism, but they did not suggest new possible pathways . After the report of catechol monoesters, researchers found that the 2-hydroxyl group in the catechol monoesters could be functionalized (masked) to inactivate the amide bond formation (Scheme c). They first used masked esters to facilitate peptide elongation and then removed the masked group to activate the esters to be polymerized or cyclized.…”
mentioning
confidence: 99%
“…However, the substrate they used to discuss was only a benzene ring without electron-withdrawing group substituents. In 1981, Vellaccio and Kemp pointed out that the basicity of the oxygen was decreased when the benzene ring was substituted with a nitro group and made it less effective at anchimeric assistance . Our group has reported an intermolecular Brønsted acid assistance peptide bond formation strategy recently .…”
mentioning
confidence: 99%
See 1 more Smart Citation